2000
DOI: 10.1034/j.1399-3003.2000.16b08.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal asthma control, starting with high doses of inhaled budesonide

Abstract: The aim of this study was to determine whether outcomes in poorly controlled asthma can be further improved with a starting dose of inhaled budesonide higher than that recommended in international guidelines.The study had a parallel-group design and included 61 subjects with poorly controlled asthma, randomized to receive 3,200 mg or 1,600 mg budesonide daily by Turbuhaler1 for 8 weeks (double-blind), then 1,600 mg . day -1 for 8 weeks (single-blind), followed by 14 months of open-label budesonide dose down-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
2
9

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 31 publications
(38 reference statements)
3
142
2
9
Order By: Relevance
“…Although not studied in the GOAL study, a number of studies have shown that long-term treatment with ICS leads to a reduction in airway inflammation and hyper-responsiveness, and a reversal in airway remodelling. [11][12][13] In the study by Ward et al, although a reduction in inflammatory cell counts was seen after three months of treatment with fluticasone propionate, improvements in airway remodelling were not seen until 12 months of treatment. 11 The effects of ICS therapy in airway remodelling are a source of controversy and this issue requires further research.…”
Section: Discussionmentioning
confidence: 98%
“…Although not studied in the GOAL study, a number of studies have shown that long-term treatment with ICS leads to a reduction in airway inflammation and hyper-responsiveness, and a reversal in airway remodelling. [11][12][13] In the study by Ward et al, although a reduction in inflammatory cell counts was seen after three months of treatment with fluticasone propionate, improvements in airway remodelling were not seen until 12 months of treatment. 11 The effects of ICS therapy in airway remodelling are a source of controversy and this issue requires further research.…”
Section: Discussionmentioning
confidence: 98%
“…29 However, the 61 patients in that study had poorly controlled asthma, and their expectations about monitoring were probably high. Reddel et al concluded that the context in which monitoring is undertaken may influence adherence and that the patients' perception of usefulness (and hence better adherence) may have been enhanced by visual presentation and discussion of graphed data at control visits every 8 weeks.…”
Section: Adherencementioning
confidence: 99%
“…Reddel et al concluded that the context in which monitoring is undertaken may influence adherence and that the patients' perception of usefulness (and hence better adherence) may have been enhanced by visual presentation and discussion of graphed data at control visits every 8 weeks. 29 We believe that, in our strictly clinically oriented setting, we had an acceptable adherence rate: our overall correlation coefficient between expected and actual days of diary-card completion (completed entries) was 0.65. Moreover, 33 (39%) of the 84 patients had 100% symptom score and PEF diary-card completion, and 68% had Ն 75% completion, which might be regarded as poor in research but is reasonably good in a clinical management setting.…”
Section: Adherencementioning
confidence: 99%
“…There is, however, no evidence that these ultra-high doses lead to better control of asthma, improve lung function or ameliorate asthma-related quality of life [23,24]. Care givers need to realise that such high doses of inhaled steroids may be associated with systemic sideeffects in the long run including adrenal suppression, skin thinning, ecchymoses, reduced bone mineral density, glaucoma and cataract [25,26].…”
Section: Inhaled Glucocorticosteroidsmentioning
confidence: 99%